Assessment of Drug Prescribing Patterns in Dermatology Outpatient Department in a Tertiary Care Hospital, Malabar, Kerala - T.K, Mohamed Saleem; C, Dilip.; V.K, Nishad (Indian Journal of Pharmacy Practice)
Skin diseases in developing countries have a serious impact on people's quality of life. Occasionally skin diseases can be a manifestation of systemic diseases. Aprospective study was carried out over six months (August 2010-January 2011) in the Dermatology outpatient department of tertiary care referral hospital in Malabar region of Kerala. A total of 500 cases were analyzed in which the total number of drugs was found to be 1230. The most commonly prescribed systemic agents were antihistamine (294) followed by antibiotics (181) & antifungal agents (49). The most commonly prescribed topical agents were topical steroids & its combination (236) followed by topical antifungal agents (124). This study reveals that generic prescription is very low and suggests that effort must be made to encourage prescribers for generic prescribing which may have a multitude of benefits including cost effectiveness. Having a steroid and antibiotic prescribing policy will go a long way to minimizing inappropriate prescriptions and also standard treatment guidelines for the treatment of common disease should be formulated.
Keywords: Skin diseases; dermatology